1986
DOI: 10.1177/002204268601600208
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol, Outstations and Autonomy: An Australian Aboriginal Perspective

Abstract: It has been argued that a variety of pressures—a history of colonial exploitation, socio-economic decline, and psycho-environmental factors—have contributed to Aboriginal alcoholism and alcohol related crime. Other analyses have connected Aboriginal drinking patterns with a well established set of social relationships which support and continue to maintain Aboriginal life-style alcoholism. In the search for effective and long-term “solutions” to this addiction the author urges a deeper understanding of Aborig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1991
1991
2008
2008

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…Autonomous cultures hold the ideal of the individual as a “rugged individualist” who is a law unto him or herself 72 . In such groups, family members and community peers respect and accept the self‐destructive behaviors chosen freely by the group member, so long as the individual does not pose a risk to others.…”
Section: Philosophical Historical Societal Cultural and Legal Dimmentioning
confidence: 99%
“…Autonomous cultures hold the ideal of the individual as a “rugged individualist” who is a law unto him or herself 72 . In such groups, family members and community peers respect and accept the self‐destructive behaviors chosen freely by the group member, so long as the individual does not pose a risk to others.…”
Section: Philosophical Historical Societal Cultural and Legal Dimmentioning
confidence: 99%
“…Herd (1989) found that black male drinkers reported a higher percentage of almost all types of alcohol-related problems than whites did. Hazelhurst (1986) noted that high rates of prob-lem drinking among the Aboriginal society seemed to be a major concern of Australian authorities. She maintained that there apparently was a higher alcohol consumption among Australian Aboriginals than in the majority population of the continent.…”
Section: The Problemmentioning
confidence: 99%
“…In general terms, poverty, the economic disparity between Aborigines and whites, lack of education and job skills are mentioned as causal factors by many writers (65)(66)(67)(68) . These factors could also, of course, be viewed partly as effects of excessive drinking, the two sets of factors being selfreinforcing [II].…”
Section: Ocio-economic Conditionsmentioning
confidence: 99%
“…Eckerman [66] points to the loss of self-esteem resulting from the social system in which Aborigines are forced to live. Boredom, unemployment, lack of hope, and feelings of rejection, anger or inferiority resulting in drinking to dull the pain are all factors cited by a number of authors [56,59,64,[67][68][69].…”
Section: Psychological Factorsmentioning
confidence: 99%